Students' Problem to Interpret Metaphor in Poems - Rahman, Nadia Mustika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
Metaphor is one of the figurative languages that important for students to understand, not only in literature works, but also in reading comprehension. Based on the pre-research observation, the students have difficulties to interpret and also to acknowledge the metaphor in poems. Therefore, the writer intends to find the students’ problem to interpret metaphor especially in poems. This research uses descriptive qualitative method, which tries to explain plainly about the students’ problem to interpret the metaphor. It was conducted at English Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. To collect the data, the research uses triangulation such as, documentations, interview, and questionnaire. The respondents of this research are 21 students of third semester at Pakuan University that formed into three groups of people. After collecting the data, the writer classifies the findings into two categories, misunderstanding and non-understanding. Based on the result, there are two groups with non-understanding problem; they clearly not understand the whole meaning of metaphor, and decided to not seek for further explanation. It can be seen by the way they missed the real metaphor that they supposed to interpret. However, two group with misunderstanding problem, they believed that they already interpret the metaphor correctly, furthermore, they do not seek for clarification to clarify their statements, whether it is right or wrong.